2022
DOI: 10.15377/2409-9813.2021.08.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Magnetized, Chelated Iron Foliage Treatments on Foliar Physiology, Plant Growth and Drought Tolerance for Two Legume Species

Abstract: A greenhouse study was conducted to determine the effects of foliar applications of magnetized, chelated liquid iron fertilizer for increasing the drought tolerance of two legumes. Study objectives were to determine the drought tolerance effects of four treatments on foliar gas exchange, soil moisture, and plant growth for velvet bean (Mucuns pruriens) and soybean (Gylcine max) plants. The four foliage treatments included applications with chelated liquid iron fertilizer (2.5 and 5%) with a conventional boom s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…In this study high leaf temperature lowered and flattened g rates under the LSM soil treatment and the 10-MT + HWT treatment (Figure 1). The gas exchange results of this study are contrary to the findings in the Reynolds-Henne drought study with legumes [53] but validated the gas exchange findings in a legume-based drought tolerance study by Ramsey [45].…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…In this study high leaf temperature lowered and flattened g rates under the LSM soil treatment and the 10-MT + HWT treatment (Figure 1). The gas exchange results of this study are contrary to the findings in the Reynolds-Henne drought study with legumes [53] but validated the gas exchange findings in a legume-based drought tolerance study by Ramsey [45].…”
Section: Discussioncontrasting
confidence: 55%
“…Partially structured water appears to maintain leaf turgor in salt stressed plants that may have had an osmotic gradient favoring extracellular water content [52]. In addition, a previous drought tolerance study by Ramsey [45] shows that a single foliage application with a magnetized sprayer, using a chelated iron solution, reduces the dry tissue biomass for immature foliage, when compared to the control treatment. In this present study, the oven dry foliage biomass is not related to water usage for the 10-MT-HWT treatments for the three soil moisture levels (Figure 6).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This follow-up article proceeds from an original article published by Ramsey [1] involving a greenhouse study with foliar spray treatments on soybean (Glycine max) and velvet bean (Mucuna pruriens) plants. This followup article presents new findings from unexplored data and analysis from the study.…”
Section: Introductionmentioning
confidence: 99%
“…The original study hypothesis and data analysis were reported in the article by Ramsey [1]. Analysis of the data in this article is based on two new hypotheses.…”
Section: Introductionmentioning
confidence: 99%